2023
DOI: 10.21203/rs.3.rs-2916139/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Affective temperaments show stronger impact on infertility treatment success compared to somatic factors, highlighting the role of personality focused interventions

Abstract: Infertility has a multifactorial background, where, besides somatic factors, psychological contributors also play a role in development and outcome. While affective temperaments have been associated with development, course, and outcome as well as treatment success in various somatic conditions, their association with infertility and its treatment has not been investigated so far. The purpose of our retrospective cohort study was to evaluate the influence of affective temperaments on fertility treatment outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The analysis included 308 women (22-46 years of age) who underwent infertility treatment within the last three years and whose treatment plan included both diet and regular physical activity. Since this study is a continuation of our previous study 32 , as a rst step, the main characteristics of this subgroup of 308 patients were compared with the entire population of 578 patients, and no statistically signi cant difference was found between the demographic, anthropometric, psychometric, and medical characteristics of the two groups except for BMI (25.83 ± 5.87 vs. 24.24 ± 4.90 kg/m 2 (W = 103380, p < 0.001)) and diagnosed metabolic disorder (79% vs. 42% (χ 2 = 108, p < 0.001)) which is a natural consequence of the fact that this group includes the patients who need to diet and exercise.…”
Section: Descriptive Statisticsmentioning
confidence: 74%
See 3 more Smart Citations
“…The analysis included 308 women (22-46 years of age) who underwent infertility treatment within the last three years and whose treatment plan included both diet and regular physical activity. Since this study is a continuation of our previous study 32 , as a rst step, the main characteristics of this subgroup of 308 patients were compared with the entire population of 578 patients, and no statistically signi cant difference was found between the demographic, anthropometric, psychometric, and medical characteristics of the two groups except for BMI (25.83 ± 5.87 vs. 24.24 ± 4.90 kg/m 2 (W = 103380, p < 0.001)) and diagnosed metabolic disorder (79% vs. 42% (χ 2 = 108, p < 0.001)) which is a natural consequence of the fact that this group includes the patients who need to diet and exercise.…”
Section: Descriptive Statisticsmentioning
confidence: 74%
“…Of the 578 patients presented in our previous study 32 , 308 had dietary and sports recommendations in their treatment plan, so they were included in this current study. The main characteristics of this subgroup of 308 patients were compared with the entire population of 578 patients using Wilcoxon rank sum tests for continuous variables and Pearson's Chi-squared tests for categorical values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to investigate this model in part due to its focus on sub-or maladaptive emotional reactions to everyday situations and events which may yield enhanced usefulness when trying to understand barriers of profiting from medical treatment, and also because previously this model has not been investigated in this context. In a previous study, we reported that affective temperaments also affect infertility treatment success 35 , and we discussed that the necessary next step is to identify the processes and factors through which they exert their influence, and which may be modifiable with psychological interventions and patient-centered, targeted therapy. A growing number of studies suggest that the role of affective temperaments in prognosis and treatment success in somatic illnesses in part may be related to their impact on complying with treatment recommendations, on the one hand, because affective temperaments influence the degree of adherence 36 , and on the other hand, because non-adherence negatively influences treatment outcome 16 .…”
mentioning
confidence: 99%